Death Of A Guru - Maharaj,Rabindranath R (Loondon Hodder & Stoughton, 1986)
Rabindranath R. Maharaj was descended from a long line of Brahamin priests and trained as a yogi. He describes vividly and honestly Hindu life and customs, tracing his difficult search for meaning and his struggle to choose between Hinduism and Christ.
Keywords: Maharaj, Rabindranath R. Christian converts from Hinduism -- Biography. Christian converts from Hinduism